Pemberian Pakan Limbah Lemuru pada Pertumbuhan Ikan Cupang (Betta splendens) - Indra Nur Cahyati; Nyoman Dati Pertami; Gde Raka Angga Kartika (Current Trends in Aquatic Science, 2022)
Betta fish (Betta splendens) is an ornamental fish that is in great demand by the community from adults to children. This fish has features such as beautiful body color, unique fin shape, and easy to maintain in a low oxygen environment. The growth rate is still slow causing the maintenance period to be relatively long so that the profits obtained are relatively small. Feeding is one of the important factors in the growth optimization process. Feed that has high protein can be used as a solution in betta fish cultivation. The feed used in the study was lemuru waste (head and bones). This study was conducted to determine the growth of betta fish (Betta plendens) fed lemuru waste feed. The study was conducted with the control jar treatment, the treatment jar A using a dose of 3%, the treatment jar B using a dose of 6%, the treatment jar C using a dose of 9%. This research was conducted for 42 days. Betta fish growth in the form of absolute weight, absolute length, specific growth rate (SGR), survival rate (SR), feed conversion ratio (FCR). Water quality parameters measured in this study include temperature, pH and DO. The results of the ANOVA study showed that survival had no significant effect on fish growth, while absolute weight, absolute length, SGR and feed conversion ratio had a significant effect on the growth of betta fish. The water quality parameters measured included temperature ranging from 27.20 to 27.69 0C, DO with a range of 3.00-3.03mg/L and a pH of 6.60-6.68.